Mental Illnesses in the Middle Ages and their Reflection in the South Slavonic Hagiographic Literature - Todorova, Ekaterina (Studia Ceranea, 2021)
The main points are related to the cultural-anthropological (Michel Foucault) and theological contextualization of diseases (Jean-Claude Larchet) and their treatment in the Middle Ages. Based on the South Slavonic hagiographic literature, the terms physician and healer are defined and specified. The study focuses on the mental disease (insanity), which according to the methodology of Larchet is three types: somatic nature of madness, the madness of demonic origin, and madness of spiritual origin. Also partly concerns the problem of God fools’ insanity.